Development path and capital structure of belgian biotechnology firms - Véronique Bastin; Albert Corhay; Georges Hübner; Pierre-Armand Michel (National Bank of Belgium, 2002)
This study investigates the relationship between the evolution of real options values and associated financing policies for Belgian companies in the sector of bio-industries. Each firm's situation regarding the relevant types of real options is stylistically represented through a scenario tree. The consumption of a time-to-build or a growth option is respectively considered as a success or a failure in company development. Empirically, several variables enable us to locate each company along the tree at any time. The study of transitions leads us to discover that failures tend to trigger higher leverage, unlike in the trade-off theory. Yet, the increases in debt maturity, in lease and in convertible financing confirm our predictions. Overall, we emphasize evidence of undercapitalization and of proper, yet insufficient, use of hybrid financing by biotech companies.
Keywords: 330; Biotechnologie-Industrie; Kapitalstruktur; Belgien